Fluoride release and recharge abilities of zinc-reinforced glass ionomer cement in comparison to traditional high strength glass ionomers - Adel Ahmed Bamoussa; Mansour K Assery; Sharat Chandra Pani (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of this study was to compare the fluoride release and recharge characteristics of a zinc reinforced glass ionomer cement (GIC) (ChemFil Rock ™, Dentsply, York PA, USA) to that of two traditional high strength GICs (Fuji IX ™, GC Corp, Japan and Ketac-Fil™, 3M-ESPE, Germany). Materials and Methods: A total of 60 specimens (20 in each group) were used in this study. The materials were prepared according to the manufacturers' instructions and placed in plastic molds 9 mm in diameter and 2 mm high. The 20 specimens in each group were further subdivided into two subgroups of 10 each. Subgroup A (control) involved no fluoride treatment. Subgroup B involved application of a 1450 ppm dentifrice for 2 min twice daily for 30 days with a soft toothbrush. The specimens were then suspended in airtight plastic bottles containing 20 ml deionized water. A fluoride electrode was used to measure fluoride release and recharge from the discs on the 1 st , 2 nd , 7 th , 15 th , and 30 th day. Results: The results of the study showed that the zinc reinforced glass ionomer had a significantly higher fluoride release and recharge when compared to conventional high strength glass ionomers. Conclusions: The results of this study suggest that zinc reinforced glass ionomers have better fluoride recharge and release characteristics than conventional high strength glass ionomer.